HUBUNGAN PENGETAHUAN IBU DENGAN SIKAP DALAM MEMILIH ALAT KONTRASEPSI INTRA UTERINE DIVICES - Dwi Herman Susilo (Prodi D III Kebidanan Fakultas Ilmu Kesehatan Universitas Ibrahimy, 2016)
Intra Uterine divices (IUD) is a long-term contraceptive methods are very effective to regulate birth spacing. Many reasons can be put forward that the IUD was developed and introduced as an effective way of birth control include the IUD as a contraceptive that has a high effectiveness in preventing pregnancy, the IUD is a contraceptive method of long-term (10 year). and IUD preferred for participants who had enough children and do not want to have more children, but not yet ready to run kontap. This is evident from a preliminary survey conducted in April 2014, using a sample of 10 EFA acceptors. The purpose of this study was to determine the relationship of maternal knowledge with attitude in choosing contraceptives IUD (Intrauterine divices) in PHC Banyuputih Sumberwaru village Situbondo. This research method using analytic descriptive cross sectional study. Samples were Mrs. EFA in PHC Banyuputih Sumberwaru village in July 2014 - January 2015 as many as 76 people (sample population). Questionnaire data retrieval techniques. Furthermore, the data were analyzed by using test